Making Melbourne’s public transport network multi-directional: Can the associated accessibility boost mobilise latent potential for ridership and city-building? - Scheurer, J.; Curtis, Carey; McCleod, S. (2016)
As in most Australasian cities, Melbourne’s public transport system has a strong radial orientation and despite the introduction of orbital SmartBus routes, displays weaknesses in facilitating cross-suburban travel. This is true for outer, middle and inner suburbs. Some intensifying CBD fringe areas also suffer from missing public transport links into adjacent neighbourhoods in a non-radial direction. Often, where orbital links do exist, they may be indirect and infrequent, aimed at servicing an excessive range of demand through meandering route structures. This situation for public transport can be contrasted with infrastructure plans for roads. For example, the controversial, now-cancelled East West Link, an inner orbital tollway project that was rationalised by a substantial forecast for road movement along its corridor, included no capacity-boosting component for public transport modes on the same route. This paper draws on the Spatial Network Analysis for Multimodal Urban Transport Systems (SNAMUTS) tool to identify the potential network function, and its impact on overall spatial accessibility, that could be achieved if a denser web of orbital tram and bus routes were added to Melbourne’s projected public transport system in 2026 (after the expected completion of the Metro rail tunnel). In a theoretical exercise along the Squaresville model popularised by Thompson (1977), Mees (2000) and Nielsen et al (2005), the benefits of public transport network multi-directionality are considered, quantified and applied to Melbourne’s real-world urban fabric. The analysis shows that missing orbital links are associated with significant unmet opportunities for public transport to attract latent demand and break into new market segments. The broader impacts of introducing additional tram and high-frequency bus routes into existing streetscapes and urban intensification areas are considered, suggesting a rethink of the design and functionality of the arterial road corridors required for such upgraded public transport infrastructures.